MODELING AND IMPLEMENTING TILING RHYTHMIC CANONS IN THE OPENMUSIC VISUAL PROGRAMMING LANGUAGE. - Agon, Carlos; Andreatta, Moreno (Perspectives of New Music)
The article focuses on tiling rhythmic canon construction used in the visual programming language, OpenMusic (OM). It states that OM enables the creation of compositional models using a graphical interface representing a musical structure and process. It says that cyclic group algebraic models describe the combinatorial feature of the equal-tempered system. It cites various examples of the tiling rhythmic canons, such as translated and augmented canons.